2017
DOI: 10.1007/s10845-017-1384-5
|View full text |Cite
|
Sign up to set email alerts
|

Smart manufacturing based on cyber-physical systems and beyond

Abstract: Cyber-physical systems (CPS) have gained an increasing attention recently for their immense potential towards the next generation smart systems that integrate cyber technology into the physical processes. However, CPS did not initiate either smart factories or smart manufacturing, and vice versa. Historically, the smart factory was initially studied with the introduction of the Internet of Things (IoT) in manufacturing, and later became a key part of Industry 4.0. Also emerging are other related models such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
107
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(109 citation statements)
references
References 52 publications
0
107
0
2
Order By: Relevance
“…It integrates Information and Communication Technologies (ICT) with manufacturing activities as intensively as possible. The goal is to fulfill some high-level functional requirements such as monitoring, as monitoring, understanding, predicting, decision-making, and adapting [2,[4][5][6][7]. To achieve the above-mentioned requirements, Industry 4.0 requires some knowledge-centric embedded systems such as the Internet of Things (IoT), the Industrial Internet of Things (IIoT), and Cyber-Physical Systems (CPS) [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It integrates Information and Communication Technologies (ICT) with manufacturing activities as intensively as possible. The goal is to fulfill some high-level functional requirements such as monitoring, as monitoring, understanding, predicting, decision-making, and adapting [2,[4][5][6][7]. To achieve the above-mentioned requirements, Industry 4.0 requires some knowledge-centric embedded systems such as the Internet of Things (IoT), the Industrial Internet of Things (IIoT), and Cyber-Physical Systems (CPS) [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…It is also found that to validate whether or not a simulated surface roughness resembles the expected roughness, the outcomes of the possibility distribution-based computing and DNA-based computing are more effective than the outcomes of a conventional computing wherein the arithmetic mean height of surface roughness is calculated. Thus, apart from the conventional computing approaches, the leading edge computational intelligence-based approaches can digitize manufacturing processes more effectively.understanding, predicting, decision-making, and adapting [2,[4][5][6][7]. To achieve the above-mentioned requirements, Industry 4.0 requires some knowledge-centric embedded systems such as the Internet of Things (IoT), the Industrial Internet of Things (IIoT), and Cyber-Physical Systems (CPS) [8][9][10][11][12].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…machines or workpieces, which combine with the digital world, i.e. sensors and intelligence, and are thus able to communicate, act and control themselves and each other (Baheti and Gill 2011;Yao et al 2017). In Thoben et al's (2017) review of the current Industry 4.0 and Smart Manufacturing initiatives they identified the standardization of both interfaces and information models as one of the most relevant research issues for smart manufacturing.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in industrial systems such as smart electric grids, there is a need of decentralised, adaptive CPSs framework towards their operative automation and optimal performance [259]. Other systems may also benefit from the use of MAS and complex networks over their CPSs, from smart manufacturing and logistics [260] to food supply chain systems [261]. • Digital twins (DT): DTs are a digital replica of physical assets and engineering systems taking into account their internal functioning and external processes that may affect their performance.…”
mentioning
confidence: 99%